2021
DOI: 10.1111/1541-4337.12880
|View full text |Cite
|
Sign up to set email alerts
|

Dietary cholesterol oxidation products: Perspectives linking food processing and storage with health implications

Abstract: Dietary cholesterol oxidation products (COPs) are heterogeneous compounds formed during the processing and storage of cholesterol‐rich foods, such as seafood, meat, eggs, and dairy products. With the increased intake of COPs‐rich foods, the concern about health implications of dietary COPs is rising. Dietary COPs may exert deleterious effects on human health to induce several inflammatory diseases including atherosclerosis, neurodegenerative diseases, and inflammatory bowel diseases. Thus, knowledge regarding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 245 publications
(356 reference statements)
0
26
0
Order By: Relevance
“…Dietary oxysterol is produced by the oxidation of cholesterol with oxygen and the reactive oxygen species (ROS) during cooking and storage of foods. Several studies showed that oxysterols are increased under conditions of microwave cooking or long-term frozen storage [ 26 , 27 , 28 , 29 ]. The main sources of dietary oxysterols are processed or stored in eggs and dairy products, and other cholesterol rich foods.…”
Section: Intake and De Novo Synthesis Of Cholesterol And Oxysterolsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dietary oxysterol is produced by the oxidation of cholesterol with oxygen and the reactive oxygen species (ROS) during cooking and storage of foods. Several studies showed that oxysterols are increased under conditions of microwave cooking or long-term frozen storage [ 26 , 27 , 28 , 29 ]. The main sources of dietary oxysterols are processed or stored in eggs and dairy products, and other cholesterol rich foods.…”
Section: Intake and De Novo Synthesis Of Cholesterol And Oxysterolsmentioning
confidence: 99%
“…Cholesterol oxidation products can already be detected in raw meat (2–11 mg/kg fat), and the concentrations rise during thermal processing (3.4–35 mg/kg fat). Egg yolk powders (441–714 mg/kg fat) and butter, as well as butter oil (13.7–27.3 mg/kg fat), are major dietary sources of cholesterol oxidation products [ 26 , 27 , 28 , 29 ]. The most commonly detected individual oxysterols in foods are C7 cholesterol oxides: 7α-hydroxycholesterol (7α-HC), 7β-hydroxycholesterol (7β-HC), and the oxidation product of both, 7-ketocholesterol (7-KC) ( Figure 3 ).…”
Section: Intake and De Novo Synthesis Of Cholesterol And Oxysterolsmentioning
confidence: 99%
See 1 more Smart Citation
“…These oxygen groups make oxidized cholesterol more polar and easier to diffuse into the cell membrane. , Previous in vitro experiments have found that oxidized cholesterols are more reactive than cholesterol itself in promoting the inflammation, oxidative stress, and programmed cell death . Meanwhile, the oxidized cholesterol-enriched diet has been blamed to be partially accountable for atherosclerosis and neurodegenerative diseases . Dietary oxidized cholesterols have been shown to exacerbate the inflammation via increasing the concentrations of IL-6 and tumor necrosis factor alpha (TNF-α) .…”
Section: Introductionmentioning
confidence: 99%
“…17 Meanwhile, the oxidized cholesterol-enriched diet has been blamed to be partially accountable for atherosclerosis and neurodegenerative diseases. 18 Dietary oxidized cholesterols have been shown to exacerbate the inflammation via increasing the concentrations of IL-6 and tumor necrosis factor alpha (TNF-α). 19 that these pro-inflammatory cytokines are involved in the progress of IBDs.…”
Section: ■ Introductionmentioning
confidence: 99%